Teológia és filozófia - NÉMETH, Tamás (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
The Relationship between Philosophy and Theology. Several viewpoints have been formulated about the relationship between theology and philosophy from antiquity to the present time. There are four known relation-ships between Christian theology and philosophy. The first one considers them contradictory to each other, the second one tries to find and show the complementary identities between them, the third one considers theology to be above philosophy, and the fourth one considers theology to be subordinated to philosophy. Today’s Christian theology considers dialogue as the only viable path. Not renouncing the absolute need of Christ’s statement to man, however, taking into account the general life vision of people and the changes in their scientific worldview, it seeks to make the message of the Gospel known, acceptable and understandable in the present. Modern Hungarian philosophy of religion seems to be a partner in this endeavour when it seizes religion as reality as a whole. Europe can only avoid religious, philosophical, cultural and scientific fragmentation if it shows a unified reality and truth in the religious sense through continuous dialogue.